Tratamientos de primera línea para pacientes estadio IV con adenocarcinoma pulmonar de mutación EGFR - Pohl V, Emilio; Pozo U, Sebastián; Poblete C, Javiera; Muñoz M, Agustín; Segura B, Francis (Revista Hospital Clínico Universidad de Chile, 2021)
Lung cancer is one of the leading causes of death in the world. Current treatments act directly on the signal transduction pathways in cancer cells, mainly. One of the main pathways is associated with the Epidermal Growth Factor (EGFR), whose mutations leads to uncontrolled cell proliferation and a higher rate of cell invasion. Activating mutations in the EGFR gene, which includes deletions in exon 19 and the L858R mutation in exon 21, were detected in most patients with non-small cell lung cancer (NSCLC). Studies of EGFR tyrosine kinase inhibitors (EGFR-TKIs) such as Gefitinib, Erlotinib and Afatinib, compared with platinum-based treatments, showed that EGFR-TKIs produce increased disease-free survival, although only in patients whose cancers harbor activating mutations in the EGFR gene. Clinical trials also demonstrated that EGFR-TKIs are effective as first-line therapies in stage IV pulmonary adenocarcinoma. Here,the main aspects of the activation of the EGFR pathway in NSCLC will be reviewed, highlighting the importance for health professionals of correctly identifying activating mutations in the EGFR gene and acting quickly at the molecular level based on aforementioned treatments.